2022
DOI: 10.31234/osf.io/4qk56
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Nomothetic Span Approach to assessing the Construct Validity of Sustained Attention Measures

Abstract: Sustained attention is frequently assessed using either objective behavioral measures, such as reaction-time variability during a task, or subjective self-report measures, such as rates of task-unrelated thought (TUT) during a task. The current studies examined whether the individual-difference overlap in these measures provides a more construct valid assessment of sustained attention ability than does either alone. Whereas prior research typically considered behavioral measures to provide convergent validity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 72 publications
(156 reference statements)
3
21
1
Order By: Relevance
“…We next imputed any RTs for each subject beyond their Median þ 3*Interquartile Range to that value. Thus, we retained as much data for each subject without undue influence of extremely long RTs (see Welhaf & Kane, 2023). This procedure resulted in < 1% of RTs being imputed for each participant.…”
Section: Arc Smartphone Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…We next imputed any RTs for each subject beyond their Median þ 3*Interquartile Range to that value. Thus, we retained as much data for each subject without undue influence of extremely long RTs (see Welhaf & Kane, 2023). This procedure resulted in < 1% of RTs being imputed for each participant.…”
Section: Arc Smartphone Assessmentmentioning
confidence: 99%
“…The study of cognitive variability over larger timescales (i.e., weeks, months, and years) in healthy aging and AD has revealed that older adults and those at risk for developing AD or already showing AD symptoms are more inconsistent across testing sessions (e.g., Bielak et al, 2019;Cerino et al, 2021;Hultsch et al, 2000;MacDonald & Stawski, 2020;Martin & Hofer, 2004;Stawski et al, 2015). However, moment-to-moment variability (over the course of several seconds, rather than hours) might serve an important role in basic psychological and everyday functional processes (Unsworth & Miller, 2021;Unsworth, 2015;Welhaf & Kane, 2023). For example, the ability to maintain consistent attention and focus over the course of several seconds is important for many everyday functions like remembering a shopping list, driving, following basic instructions, and even focusing during a conversation.…”
Section: Introductionmentioning
confidence: 99%
“…We next imputed any RTs for each subject beyond their Median + 3*Interquartile Range (IQR) to that value. Thus, we retained as much data for each subject without undue influence of extremely long RTs (see Welhaf & Kane, 2023). This procedure resulted in < 1%…”
Section: [Insert Figure 2 Here]mentioning
confidence: 99%
“…The study of cognitive variability over larger timescales (i.e., weeks, months, and years) in healthy aging and AD has revealed that older adults and those at risk for developing AD or already showing AD symptoms are more inconsistent across testing sessions (e.g., Bielak, Mogle, & Sliwinski, 2019;Cerino et al, 2021;Hultsch et al, 2000;MacDonald & Stawski, 2020;Martin & Hofer, 2004;Stawski, MacDonald, & Sliwinski, 2015). However, moment-to-moment variability (over the course of several seconds, rather than hours) might serve an important role in basic psychological and everyday functional processes (Unsworth, 2015;Unsworth & Miller, 2021;Welhaf & Kane, 2023). For example, the ability to maintain consistent attention and focus over the course of several seconds is important for many everyday functions like remembering a shopping list, driving, following basic instructions, and even focusing during a conversation.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral measures of mind wandering, including preerror speeding and reaction time (RT) variability, are often used to supplement self-reports and may actually reflect slightly different aspects of mind wandering (Unsworth et al, 2021; Welhaf & Kane, in press). For example, Unsworth et al (2021) found a latent variable correlation of 0.42 between behavioral and self-reported markers of mind wandering, suggesting an overlap but also a clear separation between constructs.…”
mentioning
confidence: 99%